Comparison of The Molecular Docking Properties of Three Potentially Active Agents - GÖRGÜLÜ, Güvenç; DEDE, Bülent (International Journal of Computational and Experimental Science and Engineering, 2023)
Antineoplastic agents are generally the drugs used to recess or prevent tumor growth which is promoted in many cases by certain factors like vascular endothelial growth factor-2 (VEGFR-2) and cyclooxygenase-2 (COX-2). These two factors seem important in angiogenesis and lymphangiogenesis in fetal, normal and neoplastic tissue. Prevention of VEGF family of proteins and cyclooxygenase-2 enzyme is a good strategy to inhibit the growth of tumor tissue eventually may give rise to recession. In this study, three potentially active and an active ligand were tested for their binding properties to two target molecules mentioned above by molecular docking study. This research is aimed to compare three different molecules according to their binding affinities, binding energies and the nature of bonds formed between the ligand and the target molecules. Showing the 3D structures will localize the fitted ligands on proteins and the possible hydrogen bonds formed were defined. Among the three proposed ligands, Ligand 1 showed the closest results to the commercial product lenalidomide®. All three ligands showed similar ∆G values and fitness scores with lenalidomide® which is an indicator of good fit, proximity and orientation with the target molecule.